619. Intestinal Microbiome Changes Associated with Immune Status and Clostridium difficile Colonization in Hospitalized Children. (26th November 2018) - Mohandas, Sindhu; Soma, Vijaya L; Ambooken, Tresa; Goldman, David; Tran, Dong-Ninh; Weinstock, George; Sodergren, Erica; Herold, Betsy C
Abstract: Background: The intestinal microbiome modulates local and systemic immune responses and may impact clinical outcomes. However, there are few studies in pediatric patients. We conducted a cross-sectional study of fecal microbiomes in hospitalized children on a single inpatient unit at Children's Hospital at Montefiore, Bronx, New York in 2016–2017 to test the hypothesis that "high-risk" children with chronic illnesses (cancer, transplant and sickle cell disease [SCD]) have decreased microbial diversity and higher rates of asymptomatic colonization with C. difficile compared with children hospitalized on the same ward but without similar risk factors. Methods: Stool was collected within 72 hours of admission from patients who provided consent and assayed for C. difficile colonization by glutamate dehydrogenase (GDH); microbiome analysis was performed by 16S rRNA sequencing. Clinical and demographic data were obtained from the EMR. Results: One hundred and six unique patients provided a sample for analysis. Sixty-nine were categorized as high-risk, including 32 SCD patients. C. difficile colonization rates were 22% and 19% in the high-risk and low-risk groups, respectively, but highest in the subset of SCD patients on penicillin prophylaxis (33%). The high-risk group had a trend toward lower microbial diversity than controls, and SCD patients exhibited a diversity index greater than other high-risk patients. Antibiotic use in the last 3 months and PPI use were associated with decreased microbial diversity across the entire study population ( P = 0.004, P = 0.007, respectively). Among children with SCD, those on penicillin prophylaxis had a trend toward decreased alpha diversity while folic acid was associated with increased diversity ( P = 0.02). SCD patients had greater quantities of Bacteroides and Parabacteroides and fewer Escherichia and Shigella than the other cohorts. Conclusion: SCD and penicillin prophylaxis might be risk factors for C. difficile colonization and intestinal dysbiosis. The implications of these findings require further, longitudinal study. Disclosures: All authors: No reported disclosures.